The role of development finance institutions (DFIs) in bringing economic stability during times of crisis: a case study of 2021 July unrest in South Africa - Mafitoe, Mapotso Justine (University of the Witwatersrand, Johannesburg, 2024)
Investment by DFIs play a positive and significant role in fostering economic growth in developing countries. However, social unrest threatens business operations; it leads to trade deficits, significant job losses and currency depreciation. Yet, no empirical research focuses on the consequences of social unrest on the operations of South African DFIs generally. This study fills this gap by exploring the impact of the July 2021 social unrest on the DFI’s ability to bring economic stability during times of crisis. A sample of 12 participants were interviewed and the data was analysed using thematic analysis. The results show that the activation and incorporation of a ‘financial intermediary’ role into the DFI’s corporate strategy precipitated organisational change and enabled the DFI to ‘rescue’ businesses post-2021 civil unrest. However, PUBRF was more than a solution to the problem of affected businesses. It was an activity that enabled the DFI to bring economic stability and job-rich industrialisation, achieve organisational growth and profitability, and develop a plan to effectively handle future critical events. The successful integration of PUBRF into the DFI’s operations confirms previous studies that organisational change capability is illustrated by an organisation’s ability to learn, anticipate future changes, and manage episodic change without compromising core organisational activities. This study recommends that organisations embrace change as it leads to enhanced relations with the environment, upskilling, coordination, flexibility, and resilience, all of which ultimately promote performance.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: DFIs; Economic stability; Social unrest; Case study; Organisational change; UCTD; SDG-8: Decent work and economic growth